(untitled) (Fiep Bulletin - online, 2013)
This paper derives from a study conducted in the framework of the Ethics and Professional Ethics Course, career in Physical Education Teacher of the National University of La Matanza - Argentina. The goal is to make a presentation of the laws of Argentina related to sport, for the purposes of analyzing the rights, obligations and sanctions contemplated therein, summarizing its central aspects. The reader may have a regulatory compendium of what legally developed in Argentina in the field of Physical Education.